Ecology of Paracoccidioides brasiliensis, P-lutzii and related species: infection in armadillos, soil occurrence and mycological aspects - Hrycyk, Marluce Francisca; Garces, Hans Garcia [UNESP]; Gimenes Bosco, Sandra de Moraes [UNESP]; Oliveira, Silvio Luis de [UNESP]; Marques, Silvio Alencar [UNESP]; Bagagli, Eduardo [UNESP] (Oxford Univ Press, 2018)
Paracoccidioides brasiliensis and the related species P. americana, P. restrepiensis, P. venezuelensis, and P. lutzii (Ascomycota, Ajellomycetaceae) are the etiological agents of paracoccidoidoimycosis (PCM), one of the most important systemic mycoses in Latin America. They are dimorphic fungi, with a mycelial life cycle in soil and a yeast phase associated with tissues of mammalian hosts. This study aimed to detect Paracoccidioides spp. in armadillo tissues and associated soil samples in three well-defined geographic areas, including the Alta Floresta, an area not only endemic for PCM in the central region of Brazil but also of probable P. lutzii occurrence, whose ecology and geographic distribution are poorly elucidated. The isolates were genotyped by sequencing ITS-rDNA and the gp43-exon-2 region, and by PCR-RFLP of alpha tubulin (tub1) gene; mycological aspects such as yeast-to-mycelial transition, growth and conidial production in soil extract agar were also evaluated. We confirmed that while armadillos are highly infected by P. brasiliensis, including multiple infections by distinct genotypes or species (P. brasiliensis and P. americana) in the same animal, the same does not hold true for P. lutzii, which in turn seems to present less capacity for mycelial growth and conidial production, when developing in a soil-related condition.
Keywords: Paracoccidioides spp.; Onygenales; phylogeny; molecular detection; Dasypus novemcinctus